2014
DOI: 10.1016/j.neuroimage.2014.04.037
|View full text |Cite
|
Sign up to set email alerts
|

What do differences between multi-voxel and univariate analysis mean? How subject-, voxel-, and trial-level variance impact fMRI analysis

Abstract: Multi-voxel pattern analysis (MVPA) has led to major changes in how fMRI data are analyzed and interpreted. Many studies now report both MVPA results and results from standard univariate voxel-wise analysis, often with the goal of drawing different conclusions from each. Because MVPA results can be sensitive to latent multidimensional representations and processes whereas univariate voxel-wise analysis cannot, one conclusion that is often drawn when MVPA and univariate results differ is that the activation pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
202
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 271 publications
(210 citation statements)
references
References 33 publications
7
202
1
Order By: Relevance
“…Other possibilities are that features will be weakened at random; that weakening reflects the introduction of noise, such that memories in the short-cue condition will show a reduced signal-to-noise ratio; or that memories will become more schematic (i.e., showing a greater influence of shared vs item-specific features). Last, recent work suggests that univariate changes can contaminate similarity measures (Davis et al, 2014), so we examined whether such a confound could account for the observed pattern of results.…”
Section: Simulation: Pattern-similarity Results Reflect Weakening Of mentioning
confidence: 99%
“…Other possibilities are that features will be weakened at random; that weakening reflects the introduction of noise, such that memories in the short-cue condition will show a reduced signal-to-noise ratio; or that memories will become more schematic (i.e., showing a greater influence of shared vs item-specific features). Last, recent work suggests that univariate changes can contaminate similarity measures (Davis et al, 2014), so we examined whether such a confound could account for the observed pattern of results.…”
Section: Simulation: Pattern-similarity Results Reflect Weakening Of mentioning
confidence: 99%
“…The legitimate enthusiasm about these methods is tempered by lingering questions regarding the interpretation of multivariate analyses 31,32 . In addition, recent work combining electrophysiology and fMRI in non-human primates has demonstrated that the sensitivity of MVPA is limited by the spatial characteristics of the neuronal representations that code for particular features, such that some kinds of neuronal patterns may be more difficult to decode using MVPA than others 33 .…”
Section: Representational Analysesmentioning
confidence: 99%
“…In particular, RSA analyses of fMRI encoding data suggest that, in some contexts, representational stability may be beneficial to later remembering (Xue et al 2010;Ward et al 2013; but see Wagner et al 2000), demonstrating that greater pattern similarity of an item's neural representations across multiple encoding trials predicts better subsequent memory for the item. Although some questions remain (Xue et al 2013;Davis et al 2014), researchers are now positioned to measure, at the individual trial level and within an individual human brain, the large-scale distributed neural representations that underlie important aspects of memory behavior.…”
Section: Multivariate Fmri Analyses and Memory Theorymentioning
confidence: 99%